Carving image: impactful Amistartop brand communication strategy and tactics - Faizal Abrudin,; Leila Mona Ganiem, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Crop protection industry grows with an increase in registration reaching 1,049 products, including 57 brands under Azoxistrobyn (AZT) category to control disease and increase grain weight. This encourages tighter and more aggressive market competition leading to challenges in Syngenta Indonesia’s AmistarTop in building brand awareness among growers. The aim of this research is to comprehensively examine brand communication strategy of AmistarTop to increase brand awareness among growers. A qualitative approach with a case study method is used by utilizing multisource data. The results indicate that AmistarTop’s brand communication applies (i) brand building approach, including mass media advertising, public relations; and (ii) brand-business approach, including digital interactive media with the brand communication umbrella "Rice is Life". Billboard is the only activity executed within mass media advertising driven by specific target. Public relations is significantly applied using a public information model through special on-field marketing events, community relations, and media relations. Digital interactive media is carried out through website and social media with informative, interactive and collaborative properties. Modifying AmistarTop's brand communication tactics includes exploration of more mass media channel, increasing public relations activities with a two-way symmetrical model approach, and intensifying digital interactive media content with patterned and scheduled uploads will enrich ways of reaching more growers and establish brand awareness.